El principio del interés superior del niño frente a lo que puede ser considerado como medidas de protección, en Guaranda, año 2023. - Quintanilla Coello Linda Celeste (2025)
The research work entitled: “The principle of the best interest of the child versus what can be considered as protection measures, in Guaranda, year 2023”. It treats as an independent variable the principle of the best interest of the child and as a dependent variable the protection measures. The principle of the best interest of the child is a guiding principle that obliges the administration of justice to make decisions that favor the rights of minors when they are in conflict with any other right, such as the rights of parents. Protective measures are a set of administrative and judicial actions aimed at safeguarding the rights of minors when it is thought that these could be violated, but beyond that, to avoid a situation of risk for the minor. The problem of the present research is presented by the criterion issued by the National Court of Justice, through Oficio No. 213-2019-P-CPJP, dated August 12, 2019, which provides that the Judge can determine the most appropriate and effective protection measures for each case, with which there is an indeterminacy on the classification of protection measures. That is why the formulation of the problem is: How can protection measures be assessed under the principle of the best interest of the child, in Guaranda, year 2023? Answering this question led the work to set as general objective: To analyze the protection measures that can be ordered under the principle of the best interest of the child, in Guaranda, year 2023. Regarding the methodology, a mixed approach was applied to address the research topic, integrating the qualitative approach that examines the arguments in the regulations, doctrine and jurisprudence; and the quantitative approach that analyzes the data obtained through surveys to experts, thus validating the theoretical part of the work, although it should be indicated that the quantitative approach was used only to elaborate the frequency tables and tabulations, because the interpretation is purely an argument. The scope of the study is descriptive in nature because it analyzes the elements XVIII by individualizing them, in order to understand the context of the variables subject to the present work; as such, its design is non-experimental because it addresses these variables within their natural context without manipulation of any kind. The information used in this work was based on the review of documents, mainly focused on: international treaties, the Constitution of the Republic of Ecuador, laws, doctrines, reports and jurisprudence; all documentary information was analyzed using the interpretative method. An analysis guide was used to examine the aforementioned documents and a survey guide was used to collect field information focused on the opinion of experts. Finally, the essential conclusions and suggestions of the project were reached. Key words: integral development of the child, legal security, state guardianship, rights of children and adolescents.